2020
DOI: 10.1017/jns.2020.22
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of glycaemic and insulin responses following tapioca resistant maltodextrin consumption in healthy subjects: a randomised cross-over controlled trial

Abstract: Resistant maltodextrin (RMD) from various sources of starch has been extensively studied. However, studies which reported the effects of tapioca RMD (TRM) on glucose and insulin response are lacking. This study investigated the effect of TRM on postprandial plasma glucose and serum insulin in healthy subjects. Additionally, satiety and gastrointestinal tolerability were also evaluated. Sixteen healthy participants received five different treatments on five separate days. Participants received 50 g of either: g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 51 publications
4
6
0
Order By: Relevance
“…In this study, a single dose of 5.4 g TRM (30% replacement) insignificantly reduced the postprandial blood glucose response in healthy individuals. The result is in line with a previous study, which reported that an up to 50% replacement of TM by TRM did not significantly reduce the postprandial incremental plasma glucose [ 9 ]. However, a total replacement of TM by TRM decreased postprandial blood glucose by exerting an inhibition of amylase activity (in vitro) [ 9 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In this study, a single dose of 5.4 g TRM (30% replacement) insignificantly reduced the postprandial blood glucose response in healthy individuals. The result is in line with a previous study, which reported that an up to 50% replacement of TM by TRM did not significantly reduce the postprandial incremental plasma glucose [ 9 ]. However, a total replacement of TM by TRM decreased postprandial blood glucose by exerting an inhibition of amylase activity (in vitro) [ 9 ].…”
Section: Discussionsupporting
confidence: 93%
“…Studies reported that incorporating resistant starch into food and beverages improved glycemic response [ 4 ], insulin sensitivity [ 5 ], triglyceride reduction [ 6 ], weight control [ 7 ], and appetite regulation [ 8 ]. In a previous study, 50 g of TRM significantly reduced the peak of postprandial blood glucose among healthy individuals when compared to 50 g of digestible tapioca maltodextrin (TM) and 50 g of glucose by 18% and 23%, respectively [ 9 ]. In addition, consumption of 34 g wheat-resistant maltodextrin daily for 12 weeks benefited glycemic control by improving plasma glucose, insulin, and HOMA-IR in overweight men [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our research also suggests MDX has better effects on glycemic control. A recent study by Astina and Sapwarobol (2020) reported that resistant maltodextrin is beneficial for reducing postprandial plasma glucose and serum insulin in healthy individuals (Astina and Sapwarobol, 2020). Our results suggests that MDX favorably affects the glycemia without affecting satiety in healthy females.…”
Section: Discussionsupporting
confidence: 56%
“…It is produced by debranching the starch structure from several sources of starch, such as corn, wheat, potato and tapioca. This process occurs at 140 to 160°C, with the addition of acids/enzymes, breaking the aÀ1,4 and aÀ1,6 glycosidic linkages and generating new aldehyde groups that will be bound to -OH groups of glucose at random positions (Jochym and Nebesny, 2017;Astina and Sapwarobol, 2020). A recent study by Ye et al (2015) demonstrated that 10 g Fibersol-2 with a meal stimulated production of satiety hormones and enhanced satiety (Ye et al, 2015).…”
Section: Introductionmentioning
confidence: 99%